E-PETITIONS AS A TOOL OF “DE-COMMUNIZATION” LAWS PACKAGE IMPLEMENTATION - Meliakov A.V. (Pressing Problems of Public Administration, 2017)
The article considers the possibilities of using electronic petitions as one of the tools for implementing the «de-communization” policy. It is shown that their use can positively affect the quality of managerial decisions of local self-government. Examples of electronic petitions on the subject of decommunization in several regions of Ukraine are given.